2013
DOI: 10.1364/ao.52.004806
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polytetrafluoroethylene (PTFE) phase transition at 19°C on the use of Spectralon as a reference standard for reflectance

Abstract: Sintered polytetrafluoroethylene (PTFE) is highly reflective and is widely used as a reference standard in remote sensing, radiometry, and spectroscopy. The relative change in output flux from a PTFE integrating sphere over the room temperature phase transition at 19°C has been measured at a monochromatic wavelength of 633 nm as 1.82±0.21%. The change in output flux was attributed to a small change of 0.09±0.02% in the total hemispherical reflectance of PTFE, caused by a change in its material density as a res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 20 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…The decrease in absorptance of PTFE/MoS 2 may be caused by the reflection of the PTFE film. 44 The band gap of the MoS 2 products was derived from the Tauc plot, implying a direct band gap of 2.42 eV. 45 Position-dependent Raman spectroscopy (Figure 2c) was performed under 532 nm laser excitation for a deep understanding of the PTFE effect on MoS 2 nanosheets.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease in absorptance of PTFE/MoS 2 may be caused by the reflection of the PTFE film. 44 The band gap of the MoS 2 products was derived from the Tauc plot, implying a direct band gap of 2.42 eV. 45 Position-dependent Raman spectroscopy (Figure 2c) was performed under 532 nm laser excitation for a deep understanding of the PTFE effect on MoS 2 nanosheets.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Figure b compares the UV–vis-NIR absorption spectra of MoS 2 nanosheets and PTFE/MoS 2 samples (located on SiO 2 /Si substrates), showing similar absorption edges. The decrease in absorptance of PTFE/MoS 2 may be caused by the reflection of the PTFE film . The band gap of the MoS 2 products was derived from the Tauc plot, implying a direct band gap of 2.42 eV .…”
Section: Resultsmentioning
confidence: 99%
“…The radiance reflected by the Spectralon panel was subject to correction by the intercalibration correction factor C f derived in Section III-D2, when applied to each of the individual foreoptics. Temperature differences between ambient laboratory and field conditions were considered unlikely to significantly affect the reflectance of the Spectralon reference standard [31].…”
Section: Field Measurementsmentioning
confidence: 99%
“…This deviation of the Spectralon panel from Lambertian is not specifically accounted for in the data analysis. Spectralon panels are typically calibrated at room temperature, Ball et al (2013) showed that there was no significant difference between measurements taken at room temperature (~20°C) and at polar temperatures despite a phase transition in the panels at 19°C.…”
Section: Spectralon Reference Panelsmentioning
confidence: 99%